The Landscape of Current Cloud Accounting Research: A Systematic Literature Review - Rodhiyah, Indah; Kesuma, Sambas Ade; Nasution, Fahmi Natigor; Erwin, Keulana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study systematically maps the recent cloud accounting literature, focusing on adoption factors, impacts on organizational performance, analytical technology implementation, and the theoretical frameworks and methodologies used in research conducted from 2024 to 2025. This study uses a Systematic Literature Review (SLR) guided by the PRISMA protocol. Data sources were obtained from the Scopus database using the single search string